FORENSIC GENETIC APPROACHES TO CRIME DETECTION USING RECOMBINANT PROTEIN METHODS - Jumaniyozov Erkin Hudayberganovich; Ganieva Nilufar Khamraevna; Boltaev Sardor (Web of Journals Publishing, 2025)
This article explores modern approaches to the use of recombinant proteins in forensic medicine for criminal investigations. It describes the main types of recombinant proteins, including polymerases, antibodies, and fluorescent markers, and their role in molecular genetic analysis. Particular attention is given to PCR, enzyme-linked immunosorbent assay, and CRISPR/Cas-based technologies for biological trace identification. Legal and ethical considerations of implementing these methods into forensic practice are discussed. The paper highlights the potential of recombinant proteins in increasing the sensitivity and specificity of forensic genetic testing and their importance in minimizing interpretation errors in evidence analysis.
Keywords: Forensic genetics, recombinant proteins, molecular forensics, DNA analysis, CRISPR, forensic medicine.